2012
DOI: 10.4172/1948-5956.1000122
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis to Treatment Interval and Outcome in Patients with Locally-Advanced Squamous Cell Carcinoma of the Head and Neck in a Veterans Affairs Medical Center

Abstract: Background: Treatment of locally-advanced squamous cell carcinoma of the head and neck (SCCHN) requires multi-disciplinary care often resulting in a prolonged diagnosis to treatment interval (DTI). This study aims to identify factors that influence DTI and to assess the impact of DTI on treatment outcomes. Methods:The medical records of 135 patients with SCCHN who were treated with definitive chemoradiotherapy between 2000 and 2009 at the Clement J Zablocki VA Medical Center were reviewed and analyzed.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Another 7 studies, found in the references of these 44 studies, were included, resulting in a total of 51 studies in this systematic review. 15-65…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another 7 studies, found in the references of these 44 studies, were included, resulting in a total of 51 studies in this systematic review. 15-65…”
Section: Resultsmentioning
confidence: 99%
“…The effect of delay on recurrence was less extensively studied with occasionally conflicting results. However, the effects of time delays on survival were often studied, with increased delay associated with decreased overall survival in 8 21,27,45,48,[57][58][59]62 of the 14 studies yy investigating at least 1 type of time interval. Similar outcomes were found for disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4,5 Time-to-treatment intervals are particularly important for patients with HNC because, as mentioned before, these tumors are relatively fast growing in an anatomically and functionally complex and delicate area. Although the effect of time-to-treatment intervals on overall survival has been variably reported, [6][7][8][9] recent large studies have demonstrated the unfavorable effects of long timeto-treatment intervals. 2,10 These 2 studies of large cohorts of patients with HNC found that overall survival was significantly lower with larger intervals between diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%